Life Coaching: A View from Buddhist Psychotherapy and Counseling - Mahatthanadull, Sanu (Journal of International Buddhist Studies, 2020)
This article aims to understand the essence of life coaching through the perspective of Buddhism in psychotherapy and counseling. The term "psychotherapy and Buddhist counseling" is a combination of concepts of both Buddhism and the principles of psychotherapy and counseling in Western psychology. The goal is to adjust behaviors, thinking to move the realm of the patients. Psychotherapy and Buddhist counseling can be conducted in 5 ways:- 1) Performing 3-steps of TIR; 2) psychotherapy based on the Four Noble Truths; 3) giving supportive, not intrusive, based on the principles of the Four Brahmavihāras; 4) using the three bhava and the thirty-one bhūmi principle as a map for traveling; 5) Ability to avoid certain types of questions. Even though life coaching is widely popular in Thai society, and is a phenomenon in a new form of psychological counseling that all Thai people are interested in. But still, it may be something new for Thai people. Some of the cases that illustrate the blemish of transparency that triggered the public’s fervor of doubt on the behaviors and ambiguity of the life coach itself are now common in Thai society. These are valuable lessons for both professional and newcomer life coaches that will continue to occur in Thai society.